[PP.19.14] THE INCIDENCE OF DYSLIPIDEMIA AMONG HYPERTENSIVE WITH AND WITHOUT DIABETES: ELEVEN YEAR COHORT. (September 2016) - Sousa, A.C.; Jardim, P.C.; Magalhães, F.G; Barroso, W.; Jardim, T.; Costa, T.; Mikael, L.; Rodrigues, R.B.; Ferreira, V.R.; Souza, H.S.; Moreira, H.G.; Neiva, T.C.; et al.
Abstract : Objective: To evaluate the incidence of dyslipidemia among hypertensive patients with and without diabetes type II in reference center for hypertensive patients. Design and method: A historical cohort study of hypertensive diabetic and non-diabetic patients on regular treatment for at least 11 years at a specialized hypertension care service. Initial assessment of the cohort in 2004 and final follow-up in 2015. Variables used: gender, age, hypolipidemic drugs in use, lipid profile. It was used the U test of Mann-Whitney and it was analyzed the association between variables using the chi-square test, with significance level of 5%. Results: Participated 139 patients (hypertensive diabetic: 55; hypertensive non-diabetic: 84). Females were predominant (55.8%). Initially the average overall age was 57.4 years and it was similar in both groups. The hypertensive diabetics proved to be more obese than those without diabetes in all segments. The use of hypolipidemic drugs increased in both groups throughout the cohort, but at the end hypertensive diabetics finished using larger amounts (10.9% at the beginning; 77.8% at the end) among hypertensive non-diabetics (3.6% at the beginning; 47% at the end) (p < 0.001). Figure. No caption available. Conclusions: During the follow-up both groups decreased lipid profile, however hypertensive diabetics at the end proved to be more dyslipidemic compared to non-diabetics. Continuous and regular treatment allows the most effective lipid control, which may assist in reducing cardiovascular events.